Pengaruh Edukasi Kesehatan Mental Berbasis Komunitas terhadap Pengetahuan dan Sikap Remaja di Desa Bangun Rejo, Kecamatan Tanjung Morawa Tahun 2025 - Nopalina Suyanti Damanik; Parningotan Simanjuntak; Sri Deviani; Siti Nurcahaya Br Angian; Retno Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
According to Riskesdas 2018, the prevalence of emotional mental disorders in Indonesia at the age of ≥15 years is 9.8%, and most cases are not detected or treated adequately. This shows the urgency of interventions that are not only curative, but also promotive and preventive (Yuliani & Rahman, 2022). Moreover, adolescents are often reluctant to be open about their psychological conditions because they are afraid of being stigmatized by their surroundings (Nugroho & Lestari, 2021). The purpose of this study was to analyze the Effect of Community-Based Mental Health Education on the Knowledge and Attitudes of Adolescents in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. This type of research is a quantitative study with a pre-experimental design using a one group pre-test and post-test design approach. The population in this study were all adolescents aged 13–18 years as many as 38 adolescents who participated in the entire series of educational programs analyzed using the paired t-test statistical test to see the differences before and after the educational program. Research Results Based on the results of education, there is a significance value <0.05 indicating that there is a statistically significant difference in knowledge and attitudes before and after the education program is given. Therefore, the alternative hypothesis is accepted, namely that there is a significant influence of community-based mental health education programs on adolescent knowledge and attitudes. There is an Influence of Community-Based Mental Health Education on Adolescent Knowledge and Attitudes in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, Sumatra Province.